2010
DOI: 10.1371/journal.pone.0014298
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heme Oxygenase-1 Can Halt and Even Reverse Renal Tubule-Interstitial Fibrosis

Abstract: BackgroundThe tubule-interstitial fibrosis is the hallmark of progressive renal disease and is strongly associated with inflammation of this compartment. Heme-oxygenase-1 (HO-1) is a cytoprotective molecule that has been shown to be beneficial in various models of renal injury. However, the role of HO-1 in reversing an established renal scar has not yet been addressed.AimWe explored the ability of HO-1 to halt and reverse the establishment of fibrosis in an experimental model of chronic renal disease.MethodsSp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
60
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 54 publications
11
60
0
4
Order By: Relevance
“…Desbuards et al 25 used hemin, an inducer of HO-1, to attenuate interstitial fibrosis in 5/6 nephrectomized rats via inhibiting TGF-b and caspase-3 expression and increasing bone morphogenetic protein-7 expression. Correa-Costa et al 26 further revealed that pretreatment or delayed treatment with hemin both reduced renal dysfunction and decreased the expression of proinflammatory molecules, fibrosis-related molecules, and collagen deposition in rats subjected to UUO. In addition, HO-2, which contributes the bulk of HO activity in the unstressed kidney, was also suspected to play a protective role in the animal kidney models.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Desbuards et al 25 used hemin, an inducer of HO-1, to attenuate interstitial fibrosis in 5/6 nephrectomized rats via inhibiting TGF-b and caspase-3 expression and increasing bone morphogenetic protein-7 expression. Correa-Costa et al 26 further revealed that pretreatment or delayed treatment with hemin both reduced renal dysfunction and decreased the expression of proinflammatory molecules, fibrosis-related molecules, and collagen deposition in rats subjected to UUO. In addition, HO-2, which contributes the bulk of HO activity in the unstressed kidney, was also suspected to play a protective role in the animal kidney models.…”
Section: Discussionmentioning
confidence: 96%
“…The protective effect of HO-1 against kidney injury is well known in a variety of animal models. 2,18,[22][23][24][25][26] We therefore performed an association study in patients with CAD to investigate whether the length polymorphism of the HO-1 gene promoter is associated with the risk of CKD.…”
mentioning
confidence: 99%
“…Mure et al 48 performed a study in 26 fetal lambs that underwent surgical UUO and found that PAX2 protein was highly expressed in the nephrogenic zone, decreasing progressively to being markedly decreased in control lamb kidneys. Murer et al 30 conducted an investigation in 17 biopsies of juvenile nephronophthisis and observed that the failure of PAX2 repression was involved in 4 , 28th day); TGF-β1 (SHO, C 1 , 14th day, C 2 , 28th day; GU, C 3 , 14th day, C 4 , 28th day); α-SMA (SHO, D 1 , 14th day, D 2 , 28th day; GU, D 3 , 14th day, D 4 , 28th day); Col-IV (SHO, E 1 , 14th day, E 2 , 28th day; GU, E 3 , 14th day, E 4 , 28th day); FN (SHO, F 1 , 14th day, F 2 , 28th day; GU, F 3 , 14th day, F 4 , 28th day); caspase-3 (SHO, G 1 , 14th day, G 2 , 28th day; GU, G 3 , 14th day, G 4 , 28th day); and cell apoptosis (SHO, H 1 , 14th day, H 2 , 28th day; GU, H 3 , 14th day, H 4 , 28th day) were observed in two groups. PAX2 and caspase-3 were also mainly located in the RTEC (red arrow for PAX2 and blue arrow for caspase-3), and the apoptotic cell in our observation was mainly derived from RTEC (black arrow).…”
Section: Mrna Expression Of Pax2mentioning
confidence: 99%
“…2,3 Unilateral ureteral obstruction (UUO) is a well-characterized model of experimental obstructive nephropathy, culminating in renal tubular apoptosis and interstitial fibrosis. 4,5 Cell apoptosis, such as renal tubular epithelial cells (RTEC) apoptosis, is a critical detrimental event that leads to chronic kidney injury in association with renal fibrosis. 6 deposition of ECM, such as collagen-IV (Col-IV) and fibronectin (FN), are the important characteristics of RIF.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, alguns estudos demonstraram que a regulação positiva da HO---1 pode inibir diretamente a inflamação. Um trabalho recente indicou que, quando a HO---1 é induzida, existe uma modulação negativa de inflamação, com a diminuição da expressão de genes e produção das proteínas de TNF---α, IL---6 e IL---1β, com concomitantes níveis aumentados da citocina imunomoduladora IL ---10 [63].…”
Section: Heme Oxigenase---1unclassified